PELATIHAN PENGOPERASIAN PROGRAM MICROSOFT EXCEL DAN POWERPOINT KEPADA PEGAWAI KANTOR DISTRIK KOKAS - Nelson Rumui; Deisya Maulida Al Hamid; Syukron Anas (Politeknik Negeri Sriwijaya, 2022)
Having 15 sub-districts and villages with an area of ​​1,128 km2, Kokas is the district with the highest number of wards and villages in Fakfak. To carry out the administrative tasks of processing data and delivering information to the public, Kokas District employees must be able to work optimally, and one of the things that is not What can be avoided is the use of computers to help improve performance and quality work output, as well as time efficiency. Therefore, this Microsoft Excel and Powerpoint operation training activity was carried out to improve the ability of Kokas District employees to perform administrative tasks of data processing and dissemination of Government policies and programs. This activity is carried out by preparing modules, providing material with practicum, as well as a final ability test. Modules and materials are provided and developed according to the needs of Partners, based on the results of discussions. During the training, the leadership and employees of the Kokas District were very cooperative and disciplined in participating in the program according to the agreed schedule.